Influence of aniline oxidative-polymerization conditions and the type of dopant on PANI particles morphology - Chmelík, Jan; Machotová, Jana; Slang, Stanislav; Zelenka, Jiří; Vlček, Miroslav (University of Pardubice, 2020)
The oxidative polymerization of aniline was studied in order to determine a favourable combination of reaction conditions leading to polyaniline (PANI) nano-sized particles of high aspect ratio and narrow polydispersity. The dimensions and morphology of PANI particles were tuned by the following reaction conditions: oxidant type, reaction temperature, reaction time, way of stirring the reaction mixture, and dopant type. The desired rod-shaped PANI morphology was achieved in the case of aniline oxidative polymerization carried out at 50 °C for 24 h and at constant stirring with a magnetic unit, when using (NH4)2S2O8 as the oxidant. The best aspect ratio under the above-mentioned conditions was reached by using HCl, p-toluenesulphonic acid, and H2SO4; all being used as dopants.
Keywords: polyaniline; oxidative polymerization; morphology